2012
DOI: 10.1021/am301060z
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Cell-Based Impedance Spectroscopy for Real-Time Probing Inhibitory Effects of Graphene Derivatives

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…On the other hand, podocytes are highly polarized cells, characterized by a dynamic actin-based cytoskeleton and small actin-based foot processes that can be rapidly remodeled upon exposure to toxins . These known differences can explain the steeper decrease in cell barrier resistance detected in the case of podocytes after 24 h. Previous studies that evaluated cytotoxic responses to graphene-based material exposure by ECIS using insect cells and HeLa cells report an adequate cell adherence indicative of biocompatibility. To the best of our knowledge, the use of ECIS to determine the barrier function of human kidney cells in response to graphene-based materials has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, podocytes are highly polarized cells, characterized by a dynamic actin-based cytoskeleton and small actin-based foot processes that can be rapidly remodeled upon exposure to toxins . These known differences can explain the steeper decrease in cell barrier resistance detected in the case of podocytes after 24 h. Previous studies that evaluated cytotoxic responses to graphene-based material exposure by ECIS using insect cells and HeLa cells report an adequate cell adherence indicative of biocompatibility. To the best of our knowledge, the use of ECIS to determine the barrier function of human kidney cells in response to graphene-based materials has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…5 suggest considerable values of the binding energy, which are consistent with the outcomes of H. Quan et al, 74 since they reported that the presence of strong electron-withdrawing groups on benzene sulfonyl 5-FU greatly enhanced the binding selectivity. 75,76 To perform accurate calculations of the transmission coefficient for the molecular junctions with sulfonyl-anchor groups, the binding energies were computed using eqn (11), for a range of diverse molecular direction within the junction (know by the © 2024 The Author(s). Published by the Royal Society of Chemistry angle Q, :C ipso -S-Au) as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because many spectroscopic assays are affected by the presence of NMs, the use of dye-free methods avoids the issues presented. For example, flow cytometry, manual cell counting techniques, electrical cell-based impedance protocols [109] or clonogenic assays [110] can be used to assess viability. A significant issue is our current inability to predict the dominant mode of interference by each NM formulation on a particular assay, therefore, each assay will be differentially affected by the type and characteristics of the NM studied.…”
Section: Recommendationsmentioning
confidence: 99%